Synthesis, Photophysical Properties and Metal Sensing Potential of Carbon Dots from Fried Onions (Global Journal of Sciences, 2025)
Using onion as a precursor and a simple hydrothermal procedure, we present a novel,  straight forward and environmentally friendly method for synthesizing highly  luminous carbon dots (CDs). The optical and physiochemical properties of the  synthesized CDs were investigated using scanning electron microscopy (SEM), X ray diffraction (XRD), Fourier transform infrared (FTIR), UV-visible, fluorescence  spectroscopy, and elemental analysis. These CDs exhibited excellent aqueous  dispersibility, excitation dependent fluorescence emission, and remarkable stability  under various conditions such as pH, high ionic strength, and continuous irradiation.  Notably, the presence of Fe2+ and Cr6+ ions result in significant fluorescence  quenching. Therefore, the CDs were employed as a fluorescent probe for the selective  detection of Fe2+ and Cr6+ ions, achieving a good linear correlation (R2 = 0.996) in  the concentration range of 0-20 μM with a detection limit of 0.31 μM. The detection  capability of these CDs for Fe2+ and Cr6+ was enhanced by their high selectivity,  photo stability, and excellent biocompatibility.
Keywords: Quantum dot; Zinc Sulphate; Photoluminescence; Limit of detection; Biocompatibility.